2019
DOI: 10.1016/j.jjcc.2019.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive assessment using the revised Hasegawa's dementia scale to determine the mid-term outcomes following transcatheter aortic valve replacement

Abstract: Over the past few decades, transcatheter aortic valve replacement (TAVR) has emerged as a less invasive alternative to surgical aortic valve replacement [1][2][3]. Although there was a tremendous survival advantage and symptom benefit for many patients undergoing TAVR, compared with medical therapy, some patients died soon after the procedures [4,5]. Recently, variable frailty markers have been developed to guide better patient selection and are considered to be essential components of patient care in TAVR [6]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 24 publications
0
41
0
Order By: Relevance
“…
The numbers of elderly patients with heart disease and with dementia in Japan are increasing and are becoming public health problems [1][2][3]. Moreover, cardiovascular disease (CVD) is strongly associated with cognitive dysfunction [4], and cognitive dysfunc-tion in patients with heart disease is associated with increased short-and mid-term progression to death and hospital readmission [5,6] and with functional disability [7].Mild cognitive impairment (MCI) is thought to be a transitional state between the normal decline in cognitive function that occurs with aging and dementia [8], and early intervention is necessary to prevent dementia from the time of MCI onset or before because 5-10 % of healthy elderly people with MCI will develop dementia [9].In the daily clinical setting, we have observed that in Japanese heart disease patients with cognitive dysfunction, brush pressure is low when writing Japanese calligraphy with a brush on a piece of paper. Previous studies reported that finger dexterity can reflect a
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
The numbers of elderly patients with heart disease and with dementia in Japan are increasing and are becoming public health problems [1][2][3]. Moreover, cardiovascular disease (CVD) is strongly associated with cognitive dysfunction [4], and cognitive dysfunc-tion in patients with heart disease is associated with increased short-and mid-term progression to death and hospital readmission [5,6] and with functional disability [7].Mild cognitive impairment (MCI) is thought to be a transitional state between the normal decline in cognitive function that occurs with aging and dementia [8], and early intervention is necessary to prevent dementia from the time of MCI onset or before because 5-10 % of healthy elderly people with MCI will develop dementia [9].In the daily clinical setting, we have observed that in Japanese heart disease patients with cognitive dysfunction, brush pressure is low when writing Japanese calligraphy with a brush on a piece of paper. Previous studies reported that finger dexterity can reflect a
…”
mentioning
confidence: 99%
“…The numbers of elderly patients with heart disease and with dementia in Japan are increasing and are becoming public health problems [1][2][3]. Moreover, cardiovascular disease (CVD) is strongly associated with cognitive dysfunction [4], and cognitive dysfunc-tion in patients with heart disease is associated with increased short-and mid-term progression to death and hospital readmission [5,6] and with functional disability [7].…”
mentioning
confidence: 99%
“…The Clinical Frailty Scale (CFS) [ 79 ] was used in n = 9 studies [ 13 , 32 , 37 , 40 , 61 , 62 , 63 , 64 , 65 ]. Short-term mortality was considered in n = 2 prospective [ 13 , 32 ] (2235 patients) and n = 1 retrospective [ 40 ] (1542 patients) studies, with contradictory results.…”
Section: Resultsmentioning
confidence: 99%
“…While two investigations [ 32 , 40 ] showed higher risk of 1-year mortality in patients with higher CFS scores, Afilalo et al [ 13 ] demonstrated no association between CFS ≥ 5 and relative risk of mortality. Long-term mortality was investigated in n = 4 prospective [ 13 , 37 , 62 , 64 ] (3387 patients) and n = 4 retrospective [ 40 , 61 , 63 , 65 ] (2269 patients) studies, presenting divergent results.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, cognitive function was evaluated by the revised Hasegawa's dementia scale (HDS-R) [17], which comprising of orientation, memory, attention/calculation and verbal uency [18]. HDS-R has been widely accepted in Asian populations in clinical and epidemiological surveys for the assessment of cognitive impairment [19]. Previous studies observed that HDS-R was similar to Mini-Mental State Examination and had better diagnostic accuracy for screening AD [20].…”
Section: Discussionmentioning
confidence: 99%